2007
DOI: 10.1186/1471-2164-8-362
|View full text |Cite
|
Sign up to set email alerts
|

Gene profile analysis of osteoblast genes differentially regulated by histone deacetylase inhibitors

Abstract: Background: Osteoblast differentiation requires the coordinated stepwise expression of multiple genes. Histone deacetylase inhibitors (HDIs) accelerate the osteoblast differentiation process by blocking the activity of histone deacetylases (HDACs), which alter gene expression by modifying chromatin structure. We previously demonstrated that HDIs and HDAC3 shRNAs accelerate matrix mineralization and the expression of osteoblast maturation genes (e.g. alkaline phosphatase, osteocalcin). Identifying other genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 40 publications
6
47
0
2
Order By: Relevance
“…Five highly up-regulated genes (Mknk2, ϩ5.84-fold; Slc9a3r1, ϩ4.59-fold; Ptpn1, ϩ2.71-fold; Socs3, ϩ2.19-fold; and Pik3cb, ϩ2.16-fold) play a critical role in insulin signaling. Slc9a3r1 stood out among these because we previously found it to be one of the most highly and consistently induced genes in MC3T3 cells treated with other HDIs (20). Increases in Slc9a3r1/Nherf1 expression in response to SAHA were confirmed by qPCR (Fig.…”
Section: Saha Enhances Osteoblast Differentiation and Induces Histonementioning
confidence: 73%
See 1 more Smart Citation
“…Five highly up-regulated genes (Mknk2, ϩ5.84-fold; Slc9a3r1, ϩ4.59-fold; Ptpn1, ϩ2.71-fold; Socs3, ϩ2.19-fold; and Pik3cb, ϩ2.16-fold) play a critical role in insulin signaling. Slc9a3r1 stood out among these because we previously found it to be one of the most highly and consistently induced genes in MC3T3 cells treated with other HDIs (20). Increases in Slc9a3r1/Nherf1 expression in response to SAHA were confirmed by qPCR (Fig.…”
Section: Saha Enhances Osteoblast Differentiation and Induces Histonementioning
confidence: 73%
“…We previously reported that HDIs promote osteoblast differentiation of MC3T3-E1 osteoblasts, primary osteoblasts, and ex vivo calvarial cultures (12) and differentially regulate expression of numerous genes in osteoblasts (20). In this study, we investigated the epigenetic events that promote osteoblast differentiation in vitro after exposure to the HDI SAHA.…”
mentioning
confidence: 99%
“…We previously showed that multiple HDACi drugs, including SAHA, significantly increase expression of the Nherf1 scaffold protein in osteoblasts (15,16,18). HDACi treatment of differentiating MC3T3 cells in our co-culture system similarly increased expression of both Nherf1 mRNA and protein (Fig.…”
Section: Osteoblasts Protect Aml Isolates From Apoptosis In a Co-cultmentioning
confidence: 99%
“…HDACi are known to directly target cancer cells by increasing expression of many proteins including those that regulate tumor suppression, DNA repair, and cell-cycle arrest. Because HDACi have also been shown to alter expression of many genes within cells of the osteoblast lineage (15)(16)(17)(18), we hypothesized that HDACi might also target the leukemic microenvironment. HDACi have been previously shown to up-regulate Nherf1 (also known as EBP-50), a scaffold protein mutated in human hypophosphatemic nephrolithiasis/osteoporosis type 2.…”
mentioning
confidence: 99%
“…Ранние изменения в экспрессии генов затрагивают также 2 рецепторных гена Wnt-пути -ФРЗ 1 и 4. Отмечено, что экспрессия RANKL усиливается при ацетилировании ги-стонов H3 и H4 в промоторе RANKL [11,12]. HDAC 1, 3, 4, 5 являются важными факторами в регуляции остеобластогенеза.…”
Section: актуальные вопросы эндокринологииunclassified